2006
DOI: 10.1111/j.1567-1364.2006.00097.x
|View full text |Cite
|
Sign up to set email alerts
|

Lovastatin possesses a fungistatic effect againstCandida albicans, but does not trigger apoptosis in this opportunistic human pathogen

Abstract: Lovastatin inhibited the growth of Candida albicans in a fungistatic way. Although it triggers apoptosis in a great variety of eukaryotic cells, including many tumour cell lines, lovastatin failed to provoke apoptotic events in this human pathogen. The fungistatic behaviour of this statin might arise from its negative influence on membrane fluidity. Because yeast-->pseudomycelium and hyphae morphogenetic transitions took place under exposure to lovastatin morphogenetic switch and apoptotic cell death must be r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 47 publications
2
47
0
Order By: Relevance
“…An inhibitor of squalene synthetase, an intermediate step in the cholesterol pathway, blocked staphyloxanthin production and attendant virulence in Staphylococcus aureus (43). Lovastatin-mediated growth inhibition has been reported for several pathogenic and nonpathogenic yeasts and one mold (31,39,44). For example, 100 M simvastatin or atorvastatin inhibited growth of four Candida species (C. albicans, tropicalis, glabrata, and parapsilosis) as well as Aspergillus fumigatus (36).…”
Section: Discussionmentioning
confidence: 99%
“…An inhibitor of squalene synthetase, an intermediate step in the cholesterol pathway, blocked staphyloxanthin production and attendant virulence in Staphylococcus aureus (43). Lovastatin-mediated growth inhibition has been reported for several pathogenic and nonpathogenic yeasts and one mold (31,39,44). For example, 100 M simvastatin or atorvastatin inhibited growth of four Candida species (C. albicans, tropicalis, glabrata, and parapsilosis) as well as Aspergillus fumigatus (36).…”
Section: Discussionmentioning
confidence: 99%
“…Development and characterization of t BOOH-tolerant C. albicans mutants A series of C. albicans clinical isolates, namely strains 4774 (sex: woman, age: 42 y, diagnosis: cardiorespiratory insufficiency, sample: urine), 8387 (sex: woman, age: 10 y, diagnosis: Langerhans cell histocytolysis, sample: oral cavity), 10934 (sex: woman, age: 45 y, diagnosis: rectal cancer, sample: cannula), 19890 (sex: woman, age: 59 y, diagnosis: thrombotic thrombocytopenic purpura, sample: tissue lesion) and 20072 (sex: man, age: 34 y, diagnosis: pancreatitis, sample: abdominal cavity drainage) randomly selected from the Strain Collection of the Department of Medical Microbiology of the University of Debrecen, was maintained on Sabouraud dextrose agar (SDA) and grown in Sabouraud dextrose broth (SDB) [8,11,12]. As described elsewhere for the tBOOH-tolerant C. albicans AF06 mutant [8], the strains were exposed to stepwise increasing concentrations of tBOOH (2 → 8 mmol l -1 ) in SDB, and the tBOOH-tolerant 4774T, 8387T, 10934T, 19890T and 20072T mutants were randomly chosen for further morphological and physiological studies [8].…”
Section: Methodsmentioning
confidence: 99%
“…Growth kinetics were also recorded in SDB by growing the strains in 100 ml shake flasks (V culture = 20 ml, pH 5.6, 28 °C, 140 rpm, starting OD 640 = 0.1) and monitoring OD 640 values spectrophotometrically for 25 h [8,11,12].…”
Section: Methodsmentioning
confidence: 99%
“…The MIC determinations vary between different laboratories but are generally in the micromolar range (lowest is 0.4 mg/ml or 0.9 mmol/l). The synergistic effect of statins together with different standard antifungal drugs has also been evaluated [30][31][32][33][34][35][36][37][38][39], and the MIC is then generally lowered, sometimes by as much as with a factor of 10. Two articles report on potent synergistic effects of statins in combination with the atypical drugs primycin [40] and suramin [41] against various moulds.…”
Section: The Clinical Problem: Fungal Infectionsmentioning
confidence: 99%
“…Notably, several of the in vitro studies reported no significant effect of statins against Candida albicans or Aspergillus spp. [33,35,42], whereas others report impaired growth of C. albicans [42], inhibition of C. albicans biofilm [43] and effects on mitochondrial DNA [44]. A recent study shows that several statins exhibit effect against dermatophytes, that is, fungal species causing skin infections [45].…”
Section: The Clinical Problem: Fungal Infectionsmentioning
confidence: 99%